Mechanism of the legal regulation of cargo transportation by the motor transport - Волкова, Аліна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article examines the mechanism of the legal regulation of cargo transportation by the motor transport and its elements. The author stands by the theory of the legal positivism and the need for uniformity of such regulation. The mentioned approach ensures the unity of the legal regulation, as well as the ability to influence elements of the mechanism: grounds of legal relations; legal position of the parties, in particular the regulation of their rights and obligations; the legal regime of the subject; types and ways to stimulate, restrictions and prohibitions; legal remedies to protect the disturbed subjective rights and legitimate interests of the parties. Contract as an individual legal act only specifies the content of these relations to its sides. The purpose of the paper is consisted of representation of developments of interpretation mechanism of legal regulation of road transport and its elements. The object of the research is studying the approaches to the concept of "mechanism of regulation" and its elements, and the subject – provision of scientific doctrine, acts of current legislation and practice of their application. Currently scientists and practitioners have been searching ways to improve the regulation of social relations in general private law and its individual institutions based on the ideas of universalization, and in Ukraine – towards adaptation to the provisions of EU law. In the carriage cargoes by motor transport within the EU it comes to observance of common rules.